Sistem Pendidikan Langgar: Potret Pendidikan Agama Islam di Lingkungan Masyarakat Desa - Hulbat, Rahmad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
The aim of this research is to find out the language education system, which includes educators and students, the objectives of language education, language education materials, language education methods, and the evaluation of language education. This research is field research with qualitative data in a portrait study design of Islamic religious education in the village community. The results of this research indicate that the education system of Langgar Nurul Yaqin and Nurul Huda in Bitin Village, Danau Panggang District, Hulu Sungai Utara Regency is illustrated in the following description: 1) Langgar educators Nurul Yaqin and Nurul Huda are Islamic boarding school alumni and Middle Eastern alumni, and there are also the Strata 1 Arabic Language. 2) Students studying at Langgar Nurul Yaqin and Nurul Huda are of various ages. 3) Langgar Nurul Yaqin and Nurul Huda's education aims to educate the public about religious knowledge. 4) Langgar Nurul Yaqin and Nurul Huda educational materials were studied, such as reading the Book of Hidayatussalikin, which is about divine knowledge (tauhid), the science of worship (fiqh), the science of cleansing the heart (tasawuf), and reading the Book of Aqidatul Awwam, which is about divine science (tawhid). 5) Nurul Yaqin and Nurul Huda's Langgar Education Method is both the lecture method and the practical method. 6) The evaluation was never carried out.